Increased identification of novel variants in type 2 diabetes, birth weight and their pleiotropic loci: 2型糖尿病与出生体重相关的新变异及共效变异位点的发现. (20th January 2017) - Zeng, Chun‐Ping; Chen, Yuan‐Cheng; Lin, Xu; Greenbaum, Jonathan; Chen, You‐Ping; Peng, Cheng; Wang, Xia‐Fang; Zhou, Rou; Deng, Wei‐Min; Shen, Jie; Deng, Hong‐Wen
Abstract: Background: Clinical and epidemiological findings point to an association between type 2 diabetes (T2D) and low birth weight. However, the nature of the relationship is largely unknown. The aim of this study was to identify novel single nucleotide polymorphisms (SNPs) in T2D and birth weight, and their pleiotropic loci. Methods: A pleiotropy‐informed conditional false discovery rate (cFDR) method was applied to two independent genome‐wide association studies (GWAS) summary statistics of T2D ( n  = 149 821) and birth weight ( n  = 26 836). Results: A conditional Q–Q plot showed strong enrichment of genetic variants in T2D conditioned on different levels of association with birth weight. 133 T2D‐associated SNPs, including 120 novel SNPs, were identified with a significance threshold of cFDR < 0.05; 13 significant birth weight‐associated SNPs, including 12 novel SNPs (cFDR < 0.05) were identified. Conjunctional cFDR (ccFDR) analysis identified nine pleiotropic loci, including seven novel loci, shared by both T2D and birth weight (ccFDR < 0.05). Two novel SNPs located at the CDK5 regulatory subunit‐associated protein 1‐like 1 ( CDKAL1 ; rs1012635; cFDR < 0.05) and adenylate cyclase 5 ( ADCY5 ; rs4677887; cFDR < 0.05) genes are of note. These two genes increase the risk of T2D and low birth weight through the pathway of the "fetal insulin hypothesis." Conclusion: Several pleiotropic loci were identified between T2D and birth weight by leveraging GWAS results. The results make it possible to explain a greater proportion of trait heritability and improve our understanding of the shared pathophysiology between T2D and birth weight. Abstract : Highlights This study demonstrates high efficiency of the conditional false discovery rate (cFDR) method in improving the identification of novel genetic variants of both type 2 diabetes (T2D) and birth weight. The findings offer novel insights into potential shared genetic mechanisms in T2D and birth weight, which may form a basis for further biological experiments and clinical replication. The study identified two novel pleiotropic loci that may be related to the processes that affect T2D metabolism and may therefore contribute to the genetic susceptibility to T2D.